2003
DOI: 10.1074/jbc.m212227200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of औ2-Adrenergic Receptor Increases Cystic Fibrosis Transmembrane Conductance Regulator Expression in Human Airway Epithelial Cells through a cAMP/Protein Kinase A-independent Pathway

Abstract: PSD-95/Dlg-A/ZO-1 (PDZ) domains play an essential role in determining cell polarity. The Na ؉ /H ؉ exchanger regulatory factor (NHERF), also known as EBP50, contains two PDZ domains that mediate the assembly of transmembrane and cytosolic proteins into functional signal transduction complexes. Moreover, it has been shown that cystic fibrosis transmembrane conductance regulator (CFTR) and ␤ 2 -adrenergic receptor (␤ 2 AR) bind equally well to the PDZ1 domain of EBP50. We hypothesized that ␤ 2 AR activation may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…Also, the direct phosphorylation of CFTR by PKA affects its intracellular trafficking (66,67) and cAMP increases CFTR expression (67) . Taken together, the evidence indicates that PKA-RII anchoring and activity at endosomes and organelles of the secretory pathway control the proper trafficking and, consequently, the steady state distribution of select polytopic apical plasma membrane transporter proteins.…”
Section: The Role Of Camp/pka In Exocytosismentioning
confidence: 99%
“…Also, the direct phosphorylation of CFTR by PKA affects its intracellular trafficking (66,67) and cAMP increases CFTR expression (67) . Taken together, the evidence indicates that PKA-RII anchoring and activity at endosomes and organelles of the secretory pathway control the proper trafficking and, consequently, the steady state distribution of select polytopic apical plasma membrane transporter proteins.…”
Section: The Role Of Camp/pka In Exocytosismentioning
confidence: 99%
“…We recently reported that airway epithelial integrity is protected from Pseudomonas aeruginosa VF by a long-acting ␤ 2 -adrenergic receptor (␤ 2 -AR) agonist (salmeterol), which is able to induce a time-dependent increase in zonula occludens (ZO)-1 protein (8) and that ␤ 2 -AR activation regulates cystic fibrosis transmembrane conductance regulator chloride channel expression, which is critical for normal functioning of epithelial cells (27). Moreover, it has been clearly demonstrated that corticosteroids control genes encoding inflammatory cytokines and adhesion molecules in respiratory epithelial cells (3,7,16,26).…”
Section: -Although Staphylococcus Aureusmentioning
confidence: 99%
“…We have also recently shown that live S. aureus and more predominantly soluble VF in contact with HAEC induce marked alterations in the transcriptional expression profile of HAEC associated with activation of the NF-B and activator protein (AP)-1 pathway, upregulation of PGE 2 and cyclooxygenase (COX)-2 expression and proinflammatory cytokine release such as . The role of the airway inflammation in the pathogenesis of chronic obstructive pulmonary diseases is well known, but the specific effects of S. aureus VF on the regulation of the inflammation have not been well defined.We recently reported that airway epithelial integrity is protected from Pseudomonas aeruginosa VF by a long-acting ␤ 2 -adrenergic receptor (␤ 2 -AR) agonist (salmeterol), which is able to induce a time-dependent increase in zonula occludens (ZO)-1 protein (8) and that ␤ 2 -AR activation regulates cystic fibrosis transmembrane conductance regulator chloride channel expression, which is critical for normal functioning of epithelial cells (27). Moreover, it has been clearly demonstrated that corticosteroids control genes encoding inflammatory cytokines and adhesion molecules in respiratory epithelial cells (3,7,16,26).…”
mentioning
confidence: 99%
“…Polymorphisms in β 2 -AR that stimulate β 2 -AR function may also upregulate mutant CFTR activity, perhaps leading to a more favorable disease course. β 2 -AR and CFTR have been colocalized in the apical membrane of airway epithelial cells [6], where a macromolecular complex comprising CFTR, β 2 -AR, and EBP50 has been identified [6,7]. CFTR and β 2 -AR interact with EBP50 through PDZ-binding motifs in the C-termini of the proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The beta-2-adrenergic receptor (β 2 -AR), a seven transmembrane-spanning G proteincoupled receptor, is activated by β-adrenergic agonists that stimulate the production of cAMP through the stimulation of adenylyl cyclase via the heterotrimeric guanine triphosphate-binding protein Gs. Beta-2-ARs have been found in a complex with CFTR and ezrin/radixin/moesin-binding phosphoprotein 50 (EBP50), and β 2 -ARs and CFTR have been colocalized at the apical membrane [6,7]. As some mutant CFTR channels retain the limited ability to conduct chloride and can be activated pharmacologically by compounds that activate or inhibit components of the PKA pathway, including β 2 -AR, phosphodiesterases, adenylyl cyclase, phosphatases, and PKA [8,9], it is also possible that polymorphisms in the genes encoding these proteins may also stimulate CFTR activity through increases or decreases in activities of the components.…”
Section: Introductionmentioning
confidence: 99%